A Dataset of COVID-Related Misinformation Videos and their Spread on Social Media. (11th June 2021) - Knuutila, Aleksi; Herasimenka, Aliaksandr; Au, Hubert; Bright, Jonathan; Howard, Philip N.
This dataset contains metadata about all COVID-related YouTube videos which circulated on public social media, but which YouTube eventually removed because they contained false information. It describes 8, 122 videos that were shared between November 2019 and June 2020. The dataset contains unique identifiers for the videos and social media accounts that shared the videos, statistics on social media engagement and metadata such as video titles and view counts where they were recoverable. The dataset has reuse potential for research studying narratives related to the coronavirus, the impact of social media on knowledge about health and the politics of social media platforms.